Affinity maturation of anti-gelsolin antibodies - Auravuo, Iines (My University, 2024)
Gelsolin amyloidosis is a hereditary protein misfolding disease caused by a point mutation. The change in amino acid composition affects the binding of Ca2+ to the plasma gelsolin leading to aberrant proteolytic cleavage, which eventually leads to the formation of the 8 kDa and 5 kDa gelsolin fragments. The fragments, mostly the 8 kDa fragment, form amyloid fibrils, which causes the symptoms of the disease. In this thesis, parental Fab 002OH A05 was affinity matured with CDRH3 and CDRL3 affinity maturation Fab libraries using phage display. After enrichment with one panning round, the enriched light and heavy chain mutations were joined together to a combinatorial library, followed by further enrichment with two more panning rounds. The enriched binders were then primary and secondary screened in immunoassays and sequenced. Based on the secondary screening results ten binders were converted to full length IgGs and expressed in mammalian cells and their biophysical properties were studied. The equilibrium dissociation constant of the parental IgG 002OH A05 to 8 kDa gelsolin fragment was measured with surface plasmon resonance to be over 250-fold lower than previously measured equilibrium dissociation constant measured in Fab format using bio-layer interferometry. The converted antibodies and parental IgG 002OH A05 had sub-nanomolar equilibrium dissociation constants which suggest that the developed antibodies have sufficient affinity for clinical use. However, the affinity improvements were generally only two-fold in the measurement. The sequenced variants had mutations only in amino acid position 125 in the CDRH3, suggesting that the other positions were already mature in the CDR3H. In the CDRL3, amino acid position 113 was mutated in all but one sequenced variant. Variants with improved melting temperatures, aggregation temperatures and decreased polyreactivity, hydrophobicity and self-interaction were identified. However, the developed antibodies were still highly self-interactive, which might cause poor pharmacokinetics in clinical use. Therefore, other regions of the antibodies could be affinity matured with mammalian display.
Keywords: affinity maturation, antibody engineering, gelsolin amyloidosis, phage display, therapeutic antibodies